Factors contributing workplace accident in manufacturing industry - Muhammad Nabil Ahnaf, Md Rizal (2020)
The purpose of this study is to analyse the factors contributing workplace accident in manufacturing industry. This study is examined the perception of technical workers includes management staffs and non-management staff in the food manufacturing company, MSM Perlis Sdn. Bhd located in Chuping, Perlis on relationship between workplace accident among workers with stress and fatigue, unsafe act, machineries and tools, design of the workplace and training procedure. A total of 137 questionnaires had been distributed to the workers in MSM Perlis Sdn. Bhd. Hypotheses for direct effect were tested using multiple regression analyses. The findings of this study showed that only unsafe act was significantly positive related to workplace accident. On the contrary, stress and fatigue, machineries and tools, design of the workplace and training procedure were not significantly positive related to workplace accident among workers. The findings in this study had provided valuable guidance for researchers and practitioners for identifying solutions that could improved safety and health in manufacturing workplace.